Imlementasi Peningkatan Status Kesepakatan Damai Menjadi Acta Van Dading Berdasarkan Perma Nomor 1 Tahun 2016 Tentang Prosedur Mediasi di Pengadilan - Ramdhani, Alvian; Guntara, Deny; Muhamad Abas (LPPM Universitas Ekasakti Padang, 2024)
At present, in the application of applicable law in Indonesia there are known two Currently, there are two types of dispute resolution procedures under Indonesian law, namely judicial and non-judicial. ADR is an application of the dispute resolution process that already exists in Indonesian society. Currently, the Arbitration and Alternative Dispute Resolution Law No. 30 of 1999 applies to how to implement the Van Dading Settlement Amendment Law based on Supreme Court Decision No. 1 of 2016, which regulates the mediation process in court and its obstacles. raises the status of Acta Van Dading. Judgment No. 1 of 2016 in arbitration court. The research method used by the author is a qualitative research method with the methods of normative legal science. The result of the research work is the implementation of Acta Van Dading based on the mediation order of the Supreme Court No. 1 2016 to raise the status of peace agreements, that is, based on an order regulating mediation as a means of peaceful. dispute resolution. Article 13 The court notes that each mediator must have a mediator's certificate issued by the Supreme Court or the Supreme Court Accredited Practitioner Status Agreement (Acta Van Dading) based on Supreme Court Order No. 1/2016, which deals with mediation proceedings in court: a) Disagreement between the parties: b) Finding of common cause: c) Absence or time limit: d) Complexity of the dispute: e) Mistrust of the mediation: f) Non fulfilment of the agreement)